2017
DOI: 10.5194/se-8-827-2017
|View full text |Cite
|
Sign up to set email alerts
|

Development of a composite soil degradation assessment index for cocoa agroecosystems in southwestern Nigeria

Abstract: Abstract. Cocoa agroecosystems are a major land-use type in the tropical rainforest belt of West Africa, reportedly associated with several ecological changes, including soil degradation. This study aims to develop a composite soil degradation assessment index (CSDI) for determining the degradation level of cocoa soils under smallholder agroecosystems of southwestern Nigeria. Plots where natural forests have been converted to cocoa agroecosystems of ages 1-10, 11-40, and 41-80 years, respectively representing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 117 publications
2
2
0
Order By: Relevance
“…This improvement can be explained by the increase of litter -and linked litter cycling -in S-cAFS over time when compared to the very low soil organic content (SOC) content and litter cycling of the initial savannahs. This was not the case in F-cAFS established in high clay content soils where a decrease in pH, K and Ca and an increase of the C:N ratio may point to a low but steady decline of soil quality and nutrient availability -results in line with the recent study of Adeniyi et al (2017). Noticeably, soil Cu concentrations seemed to increase with time at least in S-cAFS and could point to a putative soil contamination by pesticides, as farmers use copper oxide or hydroxide to treat against black pod disease (Sonwa et al, 2008;Jagoret et al, 2011).…”
Section: Soil Quality and Contaminationsupporting
confidence: 78%
See 2 more Smart Citations
“…This improvement can be explained by the increase of litter -and linked litter cycling -in S-cAFS over time when compared to the very low soil organic content (SOC) content and litter cycling of the initial savannahs. This was not the case in F-cAFS established in high clay content soils where a decrease in pH, K and Ca and an increase of the C:N ratio may point to a low but steady decline of soil quality and nutrient availability -results in line with the recent study of Adeniyi et al (2017). Noticeably, soil Cu concentrations seemed to increase with time at least in S-cAFS and could point to a putative soil contamination by pesticides, as farmers use copper oxide or hydroxide to treat against black pod disease (Sonwa et al, 2008;Jagoret et al, 2011).…”
Section: Soil Quality and Contaminationsupporting
confidence: 78%
“…It suggests that these attributes, after converging at intermediate time scales, may keep evolving in contrasting directions for S-and F-cAFS. This could be related to the different types of soils studied (Adeniyi et al, 2017) as well as farmers' differential management within a generation and between generations (Jagoret et al, 2018a) -both putatively altering ecosystem's functioning.…”
Section: S-cafs and F-cafs General Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to soil acidity, causing interference with the availability and uptake of certain nutrients, such as P [27], and the relatively low use of mineral fertilizers [30]. Our results of the farmers interviewed further confirms communications from earlier studies that have consistently shown that most Nigerian cocoa farmers do not use chemical fertilizers [31,4,32,33], hence inadequate nutrients in the soil.…”
Section: Soil Fertility Status Of the Sitessupporting
confidence: 84%